Electronic Application of Bartocar In Chronic Renal Failure Patients: A Literature Review - Arifatul Diktina, Amalia; Arofiati, Fitri (Riviera Publishing, 2022)
Chronic Renal Failure (CRF) is a slow, progressive and irreversible decline in renal function can lead to the inability of the kidneys to dispose of residual waste products and unable to maintain fluid and electrolyte balance. Hemodialysis treatment measures performed on CRF patients in order to survive. Fluid monitoring in CRF patients using telemonitoring (remote monitoring equipment), the application contains fluid control and diet to facilitate patients at home. To find out the nutritional monitoring of Chronic Renal Failure patients using the electronic application of bartocar (nutritional fluid monitoring sheet). In this literature review were use 3 data bases namely proquest, pubmed and google scholar, he last 5 years from 2016-2020. Inclusion criteria: Quantitative, qualitative and mix method research design, have communication tools such as mobile phones/computers, Based via online (smartphones and websites), Chronic renal failure undergoing hemodialysis, Free, the last 5 years 2016-2020. Exclusion criteria: Paid journals, Patients undergoing hemodialysis. From the results of the journal search obtained 35,944 English journals discussed only 10 journals discussed different topics. Electronic bartocar (fluid monitoring sheet) in patients very helpful to facilitate diet, restriction of incoming and outgoing fluids and nutrients. This mHealth app is designed to help with early diagnosis of CRF and self-monitoring. This app can be accessed via online, android 4.0/ios mobile web application and website app. Bartocar serves to help monitoring fluids and nutrients in chronic renal failure patients at home.